Percepción de la señalización y orientación espacial de los usuarios en un instituto público pediátrico de referencia nacional en Lima, Perú - Guillen-Calle, Brandon E. (2025)
Objective: To evaluate users’ perception of signage and their spatial orientation ability in a national pediatric referral hospital in Lima, Peru. Methods: An observational, analytical, cross-sectional study was conducted at the Instituto Nacional de Salud del Niño San Borja. A total of 354 parents, guardians, or caregivers of pediatric patients were surveyed. Signage perception and self-assessed spatial orientation were measured using Likert scales. Non-parametric tests and Spearman correlation analysis were performed. Results: Most respondents (88.4%) preferred asking staff for directions, while only 11.6% relied on signage or maps. No significant differences in orientation were found according to visit frequency or educational level, except for overall self-assessment scores, where males scored higher than females (7.77 vs. 6.92; p < 0.05). A moderate correlation was observed between signage perception and self-assessed spatial orientation (rho = 0.39; p < 0.001). Conclusions: Most users rely more on staff than on signage to navigate the facility. Optimizing signage and exploring more effective orientation strategies are necessary to enhance the visitor experience.